Analisis Usability Dengan Metode Heuristic Evaluation Pada Website Paperlust.Co - Muhammad Yarjullah Hanif; Handaru Jati; Nurkhamid (Department of Electronics and Informatics Engineering Education, 2023)
One of the requirements that a website must meet is good usability or ease to use. Paperlust is a website platform that facilitates designers selling their work to customers who want to print invitations. The percentage of people who visited and made purchases through the Paperlust website during 2018-2020 was 0.26%, which is still below the e-commerce industry average of 2.27%. Although many factors influence this number, usability strongly influences people's decisions to shop on a website. This study aims to analyze the usability of the Paperlust website and propose solutions to the problems found. Usability analysis in this study uses the heuristic evaluation method regarding Nielsen and Tognazzini's usability principles. Five evaluators carried out the evaluation and data collection through observation by evaluators, questionnaires, and interviews. Data analyzes quantitatively by calculating the average severity rating, frequency and percentage of problems found. This study found 86 usability problems with an average severity rating of 2.21, or the majority classified as minor problems. The proposed recommendations are improving consistency, icon conformity, information redundancy, reducing delay, providing feedback, learnability, default conditions, flexibility, information priority, and text readability.